MODEL MIND MAPPING UNTUK MENINGKATKAN HASIL BELAJAR PESERTA DIDIK TEMA 7 SUBTEMA 1 KEBERAGAMAN SUKU BANGSA DAN AGAMA DI NEGERIKU KELAS IV di SDN 08 BUAY SANDANG AJI - Erna Septiani; Toybah Toybah; Mashannuddin Mashannuddin (Universitas Sriwijaya, 2021)
AbstractThis study aimed to describe the application of the mind mapping model in improving learning outcomes of students on the theme of 7 sub-theme 1 e ethnic and religious diversity in my country, grade IV at SDN 08 Buay Sandang Aji. This research method is Classroom Action Research, which consists of stages of planning, implementation, observation, and reflection. The results showed that there was an increase in student learning outcomes. This can be seen from the students' learning mastery, starting from the first cycle with a percentage of 66,9%, in the second cycle it increased by 50%, and in the third cycle it increased by 91,6%. Based on the results of this study, it can be concluded that the application of the mind mapping model can improve the learning outcomes of fourth grade students at SDN 08 Buay Sandang Aji on the 7th subtheme 1 of the diversity of ethnic groups and religions in my country. Key Words: mind mapping model, learning outcomes AbstrakPenelitian ini bertujuan untuk mendeskripsikan penerapan model mind mapping dalam meningkatkan hasil belajar peserta didik pada tema 7 subtema 1 keberagaman suku bangsa dan agama dinegeriku kelas IV di SDN 08 Buay Sandang Aji. Metode penelitian ini adalah Penelitian Tindakan Kelas, yang terdiri dari tahap perencanaan, pelaksanaan, observasi, dan refleksi. Hasil penelitian menunjukkan bahwa terdapat peningkatan pada hasil belajar peserta didik. Hal ini dapat dilihat dari ketuntasan belajar peserta didik, mulai dari siklus I dengan persentase sebesar 50%, pada siklus II meningkat sebesar 66,9%, dan pada siklus III meningkat sebesar 91,6%. Berdasarkan hasil penelitian tersebut dapat disimpulkan bahwa penerapan model mind mapping dapat meningkatkan hasil belajar peserta didik kelas IV SDN 08 Buay Sandang Aji pada tema tema 7 subtema 1 keberagaman suku bangsa dan agama dinegeriku. Kata Kunci: model Mind Mapping, hasil belajar